Clinical Characteristic of Bloody Diarrhea in Under- Five Pediatric Inpatients - Steven Christian Susianto; Alpha Fardah Athiyyah; Anak Agung Putri Nadia Paramitha; Eko Budi Koendhori; Khadijah Rizky Sumitro; Andy Darma; Reza Gunadi Ranuh; Subijanto Marto Sudarmo (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Diarrhea is the most common cause of death in under-five children. Bloody diarrhea comprises around 10% of all cases of diarrhea and may lead to severe complications until death. This study examined the characteristics of bloody diarrhea in children under five years old in Dr. Soetomo General Hospital Surabaya from 2013 to 2017. Material and Methods: A retrospective, cross-sectional study was conducted using secondary data from Dr. Soetomo General Hospital's inpatients with bloody diarrhea from 2013 to 2017. Gender, age, nutritional status, clinical symptoms, degree of dehydration, and laboratory results were assessed, and the data were presented in percentage (%) Results: Fifty-six samples were included in this study. The main demographics were male (58,9%), aged 7-24 months (44,6%), and normal nutritional status (66,1%). Meanwhile, the most notable manifestations were stool mucous (55,3%), mild to moderate degree of dehydration (60,7%), and leukocytosis (62%). Eleven patients (39,2%) had temperatures ≥380C. Leukocytes were positive in 93.7% of the stools. Furthermore, amoeba was found in 46,8% of samples. The serum electrolyte result showed hyponatremia (18%) and hypokalaemia (15%). Conclusion: The primary demographics of bloody diarrhea in under-five children admitted to Dr. Soetomo General Hospital were males, 7-24 months of age, and with normal nutritional status. The most frequent manifestations were mucous in stool, mild to moderate dehydration, leucocytosis, as well as positive leucocytes and amoeba in the stool.